Acroshaw: Forgotten, but not Forgiven. Issue 1 (2nd January 2018) - Parnell, Stephen
Abstract: Between the Standard Catalogue Company selling AD and Andreas Papadakis's Academy Editions buying it in 1977, the magazine was owned for a year by an off-the-shelf company called Acroshaw, set up by the editors Martin Spring and Haig Beck. This precarious year, when AD was perilously close to closing down, is forgotten in history, but was definitive in turning the previous champion of neo-avant-garde movements such as Brutalism, Cedric Price and Archigram into the mouthpiece of Charles Jencks and Post-Modernism. Through oral history, biography and previously unseen notes taken by Spring at the time, this article recounts this fateful year in detail. It describes the struggles between the uncomfortable ménage à trois of Spring, Beck and Papadakis, demonstrating how an acute business acumen prevailed over architectural idealism in the battle to define architecture.